TAM Approach: Application of Si APIK to MSEs - Nunuk Latifah; Anna Widayani; Ika Rachmawati; Rani Arifah Normawati (Apollo: Journal of Tourism and Business, 2023)
The ever-growing technology makes innovations about financial applications, so financial application applications continue to innovate. This has made micro, small and medium enterprises (MSMEs) adopt financial bookkeeping to run their businesses. Bank Indonesia launched an Android-based financial application that can be obtained for free. The application is the Financial Information Recording Application Information System (SI APIK). This study aims to examine MSMEs in using the Si APIK application in managing their business. The method and conceptual formulation model were carried out in several stages; literature study, model adoption, and instrument development. Based on theoretical and empirical studies of the Technology Acceptance Model (TAM), this study describes the constructs and propositions used as the basis for building a conceptual model. The results of instrument development can be used for further research